KAJIAN TENTANG PRINSIP MODEL PENCATATAN LAPORAN KEUANGAN DALAM PERSPEKTIF AL-QUR’AN - Ifa Hanifia Senjiati; N. Eva Fauziah (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2015)
ABSTRACT : Recording of financial statements that have been made, both individually and institutions (especially microfinance) didn‟t disclouse financial statements properly. This is caused by alack of understanding of human resources for the recording of the financial statements. Human resources there are not easy to understand the concepts and principles accounting as regulated financial accounting standards, as shown by the fact tha tthe results of the training to the public and the results of research on the Financial Statements of Cooperation Islamic Financial Services Based on this phenomenon, to make it easy for accountants (recorder) recording the model prepared financial statements derived from the AL-Quran with monotheism foundation that gave spawned to the operational principle of the model KITAB consist in Kerjakan, Istiqamah, Tulis, Adil dan Beruntung.